Is it still current to talk about first ray hypermobility? - Alfieri Montrasio, Umberto; Corbo, Valentina; Mangiavini, Laura; Palmucci, Maria (Acta Biomedica Atenei Parmensis, 2019)
Since the time of D. Morton in clinical evaluation we talked about the concept of hypermobility as a cause of diseases such as hallux valgus. To date, this concept has been deepened in order to better understand the pathological mechanisms that create deformity, in order to identify the most appropriate prevention and correction procedures. Physics introduced the concept of stiffness, a property that also belongs to the podalic structures. Changing the terminology is difficult, but the knowledge of biomechanics requires the elimination of the term hypermobility because it resultsinconsistent with the physics applied to the foot, in favor of the terms stiffness and compliance. These clarifications make it possible to us to deepen even more specific and timely therapeutic choices, thus reducing the risk of iatrogenic complications which follows interventions on the first ray.